Global value chains: surveying drivers and measures - Jo\~ao Amador; Sónia Cabral (European Central Bank (ECB), 2014)
The production of most goods and services is nowadays vertically fragmented across different countries, as global value chains (GVCs) emerged as the current paradigm for the international organisation of production. This paper surveys part of the growing empirical literature on GVCs, starting by discussing the main driving forces of GVCs in recent decades. Next, it surveys the indicators used to map and measure this phenomenon, accounting for their different scopes and required datasets.
Keywords: F60; 330; global value chains; globalisation; International trade; offshoring; survey